2013
DOI: 10.4181/rnc.2013.21.820.8p
|View full text |Cite
|
Sign up to set email alerts
|

Somatisation and Dissociation: A Comparison Study In Bruxers Subgroups

Abstract: de 11,8, 9,6 e 16,3 no grupo com bruxismo e Distúrbios temporomandibulares e de 2,6, 4,8, e 10,4 no controle (Somatização entre os dois grupos p<0,0001 e para dissociação p<0,0001). Os valores em somatização e dissociação foram de 9,6 e 16,3 (grupo experimental p<0,0001) e 4,8 e 10,4 (grupo controle p<0,0001), . Os valores em somatização (6,2, 9,6, 10,7, e 11,8 p=0,0001) e dissociação (10,6,16,4,15,2 e 27,1 p=0,0001) aumentaram no bruxismo mais intensamente que no grupo experimental. Bruxismo, somatisação e di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…As the rage and frustration increased, patients had additional need to control their anger, resulting in more intense bruxism and psychosomatic disorders. The outcome in the current study is additionally supported by one investigation 5 demonstrating that scores in somatization, indicating anger-taken inward are higher in those demonstrating CMDs and BB signs and symptoms.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…As the rage and frustration increased, patients had additional need to control their anger, resulting in more intense bruxism and psychosomatic disorders. The outcome in the current study is additionally supported by one investigation 5 demonstrating that scores in somatization, indicating anger-taken inward are higher in those demonstrating CMDs and BB signs and symptoms.…”
Section: Discussionsupporting
confidence: 78%
“…Data in the current investigation indicate that aggressive events were reported more frequently in the CMDs and BB group and decreased progressively in the direction of the control non-dysfunctional non BB subgroup. In previous studies CMDs and BB individuals were considered as psychologically/ psychiatrically disturbed 2,5,7 . It may be that CMDs and BB individuals as a group are those characterized by high levels of anxiety, depression, and somatization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that biofeedback cannot be based on a sleep interrupting stimulus. The stimulus in the form of CES (contingent electrical stimulation) may also cause local effects, including biochemical changes [63,64]. Disadvantages of that type of treatment may comprise increasing fatigue and daytime sleepiness as a result of waking during night rest [65].…”
Section: Biofeedbackmentioning
confidence: 99%